Chlorhexidine delivery system from titanium/polybenzyl acrylate coating: Evaluation of cytotoxicity and early bacterial adhesion - Cortizo, María Cecilia (2012)
Objectives: The formation of biofilms on titanium dental implants is one of the main causes of failure of these devices. Streptococci are considered early colonizers that alter local environment favouring growing conditions for other colonizers. Chlorhexidine (CHX) is so far the most effective antimicrobial treatment against a wide variety of Gram-positive and Gram-negative organisms as well as fungi. This study was designed to develop a CHX delivery system appropriate for healing caps and abutments, with suitable drug release rate, effective as antimicrobial agent, and free of cytotoxic effects. Methods: Polybenzyl acrylate (PBA) coatings with and without CHX (Ti/PBA and Ti/PBA-CHX, respectively) and different drug loads (0.35, 0.70, and 1.40%, w/w) were assayed. The cytotoxic effect of CHX released from the different substrates on UMR106 cells was tested by alkaline phosphatase specific activity (ALP), and microscopic evaluation of the cells. Noncytotoxic drug load (0.35%, w/w) was selected to evaluate the antimicrobial effectiveness of the system using a microbial consortium of Streptococcus species. Results: The kinetic profile of CHX delivered by Ti/PBA-CHX showed an initial fast release rate followed by a monotonic increase of delivered mass over 48 h. The number of attached bacteria decreased in the following order: Ti > Ti/PBA > Ti/PBA-0.35. Conclusions: PBA-0.35 coating is effective to inhibit the adhesion of early colonizers on Ti without any cytotoxic effect on UMR-106 cells.